James White - Mond, Josh; Erdély, Mátyás; Abbott, Christopher; Nixon, Cynthia; Mescudi, Scott (Soda Pictures, 2016)
James White (Christopher Abbott) is a troubled twenty-something trying to stay afloat in a frenzied New York. His self-destructive hedonistic lifestyle leaves him unable to cope as his mother (Cynthia Nixon) battles a serious illness. James is forced to take control of his life, and must find new reserves of strength or risk imploding completely. [www.amazon.co.uk]